The Role of Leadership (Leaderpreneurship) in Building Business Creativity and Innovation - Dicky Hibbul Wathan; Sandi Fadhlurrohman; Faqih Eldayyan; Haidar Hanif Kurniadi; Naura Adhiratna; Ahmad Dzaki Yasykur; Sugiharto S (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
From an Islamic perspective, leadership and motivation are two essential elements that are interrelated in shaping the quality of organizations and individuals. Islamic leadership can be understood as spiritual, requiring the application of the values of justice, honesty, deliberation, trustworthiness, concern for the welfare of the community, and the ability to manage and direct. On the other hand, motivation functions as a driving force that influences behavioral consistency, direction, and intensity in achieving success. This paper reviews the concept of Islamic leadership, the factors that influence motivation, as well as theories of motivation and achievement motivation, then relates them to the practice of Islamic entrepreneurship. Through a review of literature and history, the discussion shows that the integration of Islamic leadership and achievement motivation creates an entrepreneurial model focused on blessings and halal profits. This principle has been proven to be able to produce an ethical, just, and sustainable economic system.